2005
DOI: 10.1029/2004tc001750
|View full text |Cite
|
Sign up to set email alerts
|

Two‐stage exhumation of midcrustal arc rocks, Coast Mountains, British Columbia

Abstract: New geologic data from the Central Gneiss Complex along Douglas Channel help delineate the burial and exhumation of the Late Cretaceous to Eocene Coast Mountains magmatic arc. Arc plutonism was on going between ∼90 and 60 Ma, replaced by formation of dikes to 52 Ma. Supracrustal rocks were buried to midcrustal levels by 90 Ma, and garnet and kyanite grew from ∼90 through 70 Ma. Subsequent exhumation was nearly isothermal and took place in two stages. The first occurred from ∼70 to 59 Ma as the arc contracted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(85 citation statements)
references
References 104 publications
2
83
0
Order By: Relevance
“…This means that such south-directed thrusting may have been strengthened by the northward subduction of the Neo-Tethyan Ocean lithosphere beneath the southern Lhasa subterrane and thus cannot be considered as a strong argument for the northward subduction of the Tethyan Bangong Ocean lithosphere beneath the Qiangtang Terrane.The absence of the Early Cretaceous high-grade metamorphic rocks along the Bangong suture zone may be attributed to the low degrees of exhumation, analogous to absence of such rocks in parts of the Coast Mountains arc in western North America(Rusmore et al, 2005) and/or to the presence of a sedimentary cover as interpreted for the lack of Jurassic granitoids in places in the western Qiangtang subterrane(Guynn et al, 2006). However, these two possibilities are less likely because no Early Cretaceous high-grade metamorphic rocks have been documented along the entire Bangong suture zone despite the fact that (1) the sedimentary cover for the western Qiangtang subterrane is only ca.…”
mentioning
confidence: 96%
“…This means that such south-directed thrusting may have been strengthened by the northward subduction of the Neo-Tethyan Ocean lithosphere beneath the southern Lhasa subterrane and thus cannot be considered as a strong argument for the northward subduction of the Tethyan Bangong Ocean lithosphere beneath the Qiangtang Terrane.The absence of the Early Cretaceous high-grade metamorphic rocks along the Bangong suture zone may be attributed to the low degrees of exhumation, analogous to absence of such rocks in parts of the Coast Mountains arc in western North America(Rusmore et al, 2005) and/or to the presence of a sedimentary cover as interpreted for the lack of Jurassic granitoids in places in the western Qiangtang subterrane(Guynn et al, 2006). However, these two possibilities are less likely because no Early Cretaceous high-grade metamorphic rocks have been documented along the entire Bangong suture zone despite the fact that (1) the sedimentary cover for the western Qiangtang subterrane is only ca.…”
mentioning
confidence: 96%
“…Combined, the structures record transpression with a dominantly sinistral component into midCretaceous time and a dextral one after then. The last stage of CCO evolution involved transtension, recorded by Eocene (~55-45 Ma) normal faults in the eastern Coast Mountains (and widespread to the east across southern British Columbia) that are in part coeval with movement on major dextral strike-slip faults (Coleman and Parrish 1991;Rusmore et al 2005).…”
Section: Coast Mountains: Core Of the Coast-cascade Orogen (Cco)mentioning
confidence: 99%
“…Agreement between the modeled and observed trends in hornblende ages might be improved if the duration of reheating is longer. Rusmore et al (2005) showed that magmatism in the Central gneiss complex, south of our study area and just east of the Quottoon plutonic complex, was nearly continuous from 90 to 67 Ma, followed by rapid cooling of the entire complex at $52 Ma. Closest to our study area, the Quottoon plutonic complex gives a U-Pb zircon age of 58.6 ± 0.8 Ma (Gehrels et al, 1991).…”
Section: Discussionmentioning
confidence: 96%
“…Crawford et al (1999) conclude that the Quottoon plutonic complex was emplaced as a series of individual intrusions which would increase the duration of reheating relative to a single intrusion. Also, the timing of metamorphism in the Central Gneiss Complex indicates relatively high temperatures until $52 Ma (Rusmore et al, 2005). An increase in the duration of reheating would increase maximum temperatures reached near the thermal boundary, and increase the distance at which hornblende 40 Ar/ 39 Ar ages are affected.…”
Section: Discussionmentioning
confidence: 97%